Efektifitas media Tangram dalam meningkatka kemampuan mengenal bangun datar pada anak berkesulitan belajar - Mayalis, Siti (journal of residu, 2019)
This research is to find out the process of increasing the ability to recognize flat shapes through Tangram and to prove thant Tangram learning is effective in increasing the ability to recognize flat shape in children with learning difficulties in 4 grade SD N 15 Bukit Bais, Solok Regascy. This Research use the Single Subject Research (SSR) research method. This study consisted of three conditions, namely the first baseline condition (A1), the second intervention (B) and the third baseline (A2). In this study data collectionn techniques using data collection with tests and direct observation. The result obtained that by using Tangram can improve the ability to recognize flate wake in children with difficulty learning 4 grade SD N 15 Bukit Bais. Keywords: Knowing Flat Build, Children with Learning Diffculties, Tangram